Broadband Near-Infrared Reflective Film from Stacked Opposite-Handed Chiral Liquid Crystals with Pitch Gradients - Hyeon Seong Hwang; Jongsu Lee; Byungsoo Kang; Minhye Kim; Doyo Kim; Se-Um Kim (Crystals, 2025)
Broadband near-infrared (NIR) reflective films are widely used in architecture and the automotive and aerospace industries for energy saving and thermal regulation. For large-area and flexible applications, it is essential to develop cost-effective, solution-processable, and long-term-stable NIR-reflective films. Here, we present a polymer-stabilized chiral liquid crystal (CLC) film that achieves broadband NIR reflection by stacking opposite-handed CLC layers with pitch gradients. We experimentally established optimal formulations of materials for both right-handed and left-handed CLCs. The resulting film exhibits high-degree broadband reflection (~95%) in the 1000–1800 nm wavelength range, while maintaining visible transmittance (~80%) in the 450–850 nm range. The concept proposed here will be widely applicable for scalable and practical NIR-filtering applications in smart glasses, sensors, and optoelectronic devices.